ANALISIS PERMINTAAN PERMINTAAN MASYARAKAT TERHADAP PRODUK KOSMETIK ORIFLAME DI KOTA PEKANBARU - Alfionita. M. Siahaan; Sri Endang Kornita; Deni Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the factors that influence the level of demand for cosmetic products Oriflame in Pekanbaru. The population numbered 287.616 people and a sample of 100 people was determinate by the method slovin. The data used in the secondary and primary. The analysis method use is descriptive analysis using ordinal scale (likert scale) to classify the measured variables in order to avoid errors in determining the outcome of the data. From the results of the testing that has been done , which uses the entire free variable that consumer tastes consisting of branding, packaging and labeling , future expectations , quality , price and the price of other goods that affect people in Pekanbaru in choosing cosmetic products cosmetics Oriflame as they use . From the research that has been carried out that almost all the indicators of consumer tastes variables affect demand for cosmetic products Oriflame seen from the highest score is the quality with a score of 2,040 and the lowest score enough influence is the display / layout with a score of 642. Meanwhile, variable price of goods itself affect the demand for cosmetic products Oriflame with a score of 1490 and other variables also affect the price of goods with a score of 703 , thus it can be concluded that the most influential is the quality that is seen from the highest score to the continuum line.Keywords : Demand, Consumer tastes, Cosmetic, Price, and Price itself.